Assessing the impact of a Vi-polysaccharide conjugate vaccine in preventing typhoid infection among Bangladeshi children: A protocol for a phase IIIb trial - Theiss-Nyland, K; Qadri, F; Colin-Jones, R; Zaman, K; Khanam, F; Liu, X; Voysey, M; Khan, A; Hasan, N; Ashher, F; Farooq, Y; Pollard, A; et al. (Oxford University Press, 2019)
Typhoid fever illnesses are responsible for more than 100 000 deaths worldwide each year. In Bangladesh, typhoid fever is endemic, with incidence rates between 292-395 per 100 000 people annually. While considerable effort has been made to improve access to clean water and sanitation services in the country, there is still a significant annual typhoid burden, which particularly affects children. A typhoid conjugate vaccine (Vi-TCV) was recently prequalified by the World Health Organization and recommended for use, and offers the potential to greatly reduce the typhoid burden in Bangladesh. This study is a double-blind, cluster-randomized, controlled trial of Vi-TCV in a geographically defined area in Dhaka, Bangladesh. At least 32 500 children from 9 months to <16 years of age will be vaccinated and followed for 2 years to assess the effectiveness and safety of Vi-TCV in a real-world setting. All cluster residents will also be followed to measure the indirect effect of Vi-TCV in this community. This protocol has been approved by the International Centre for Diarrhoeal Disease Research, Bangladesh; a University of Oxford research review; and both ethical review committees. Informed written consent and assent will be obtained before enrollment. Vi-TCV has been shown to be safe and effective in previous, smaller-scale studies. The results of this study will be shared through a series of peer-reviewed journal articles. The findings will also be disseminated to the local government, stakeholders within the community, and the population within which the study was conducted. This trial is the largest and only cluster-randomized control trial of Vi-TCV ever conducted, and will describe the effectiveness of Vi-TCV in an endemic population. The results of this trial may provide important evidence to support the introduction of TCVs in countries with a high burden of typhoid. ISRCTN11643110.